Effects of the stress-related neuropeptides urocortins on colonic epithelial barrier function - Karo, Aaron (My University, 2019)
Urocortins (Ucn1, Ucn2, and Ucn3) belong to the corticotropin-releasing factor (CRF) peptide family which exert their actions on two CRF receptors subtypes (CRF1 and CRF2). Ucn1 binds to CRF1 and CRF2, whereas Ucn2 and Ucn3 bind to CRF2. CRF has been implicated in stress-stimulated impairment of intestinal barrier function, but the effects of urocortins on intestinal epithelial barrier function remains unclear. The aims of the study were to investigate the role of urocortins on intestinal epithelial barrier function, and determine which CRF receptor subtype(s) mediates the effects of urocortins. In Ussing flux chambers, transepithelial resistance (TER) and flux of horseradish peroxidase (HRP), were measured as an indicator of paracellular permeability and transcellular permeability, respectively. Application of all three urocortins caused a decrease of TER, and increase in HRP flux, in concentration-dependent manners. Ucn2- and Ucn3-induced TER reduction was only inhibited by the CRF2 antagonist. Ucn1-, Ucn2-, and Ucn3- induced increase of HRP flux was only inhibited by the CRF2 antagonist. In conclusion, all three urocortins induce disturbances of colonic epithelial barrier function, which mimic the effects of stress and CRF. The effects of urocortins are mediated by the CRF2 receptors, which suggest the CRF2 receptors are regulating colonic barrier function.
Keywords: Cytology; Physiology; Biology